Isolation of Candida albicans and Evaluation of Plant Extracts for Antifungal Activity. - M. El-Bashic, Aisha; AB. Matter, Hamdy (Scientific Journal of University of Benghazi, 2025)
Candida albicans (C. albicans) is a common opportunistic fungal pathogen trustworthy for a variety of infections, especially in immunocompromised individuals. The increasing resistance to antifungal agents necessitates the search for alternative treatment options. In this study, we isolated C. albicans from clinical and environmental samples and evaluated several plant extracts, such as Allium sativm, salvia rosmarinus, Mentha, which we believed possessed antifungal activity. These plant extracts were tested for their ability to inhibit C. albicans growth using standard laboratory assays. Various plant extracts, including Allium sativm, salvia rosmarinus, Mentha yielded very similar results in terms of fungal inhibition, with the exception of the disc impregnated with peppermint extract, where no area of inhibition was observed. Several extracts exemplified promising inhibitory effects on fungal growth, suggesting that compounds derived from Allium sativm, salvia rosmarinus, Mentha could offer useful possibility or complement to current antifungal treatments. These findings paved the way for growth of plant based therapies to conflict drug reluctant fungal infections. The extracts exhibited great antifungal effects, notice on their potential as natural curative agents. These findings would assist further research into plant compounds as other possibility or complements to traditional antifungal drugs.